Tuberous Sclerosis in a Child - Baghel, B (Journal of Nepal Paediatric Society, 2012)
A female child presented with the complaints of seizure and learning difficulties. On examination various types of skin lesion were found, including adenoma sebacum, hypomelanic macules ("ash leaf spots"), Shagreen patches. On investigation, CT scan of brain showed subepedymal nodule in walls of ventricle. B scan of eyes revealed multiple tiny nodular lesions in posterior chamber of eyes called astrocytic hamartomas (or "phakomas"). Antiepileptic drugs started, now patient is seizure free. J Nepal Paediatr Soc 2012;32(2):181-183 doi: http://dx.doi.org/10.3126/jnps.v32i2.5829